VALIDITY OF COLOUR DOPPLER ULTRASONOGRAPHY WITH D-DIMERS IN CLINICALLY SUSPECTED DEEP VENOUS THROMBOSIS OF THE LOWER LIMB: Colour Doppler Ultrasonography & D-Dimer in DVT - Babar, Maj Taimoor Hussain; Nafees, Muhammad; Sarwar, Shakil; Ashraf, Naveed (Pakistan Armed Forces Medical Journal, 2010)
Objective: This study was designed to evaluate the validity of colour Doppler ultrasonography with D-dimers in clinically suspected deep venous thrombosis of the lower limb.Study Design: Validation studyPlace and Duration of study: Radiology Department CMH/MH Rawalpindi Six months from 15 June 2006 to 31 December 2006.Subjects and Methods: Thirty cases of clinically suspected deep venous thrombosis of the lower limb were included in the study selected on non probability convenience sampling technique. Colour Doppler ultrasonography examination of the affected lower limb was carried out and results compared with D-dimers assays results.Results: Among 30 patients who underwent colour Doppler ultrasonography examination of the affected limb for diagnosis of deep venous thrombosis, 27 (90%) were diagnosed to have deep venous thrombosis, 3 (10%) were diagnosed not to have deep venous thrombosis. Amongst them 2 patients had raised D-dimers levels and repeat Doppler ultrasound advised. On revised ultrasound deep venous thrombosis in these patients was confirmed. This showed that colour Doppler ultrasonography examination has sensitivity of 93.1%, specificity 100%, positive predictive value 100%, negative predictive value 33.33% and overall accuracy of 93.33 %.Conclusion: Colour Doppler ultrasonography has a high diagnostic yield in cases of deep venous thrombosis of lower limb when used in conjunction with D-dimers assays.